Pengenalan Transaksi Digital: Upaya Meningkatkan Literasi Keuangan Masyarakat Desa Karang Panggung - Saputra, Irawan; Zulhija, Shela Rahmat; Hestika, Dela; Apriyanti, Mike; Zalianti, Olvy Dica; Resmana, Rifky Tria; Barika (UNIB Press, 2024)
The development of information and communication technology has driven significant changes in the financial system, including the adoption of digital transactions as an alternative to cash transactions. transactions. However, the low level of digital financial literacy in rural communitiesis an obstacle in optimally utilising this technology. Through socialisation and education on non-cash transactions, this community outreach programme aims to increase the digital literacy of the programme aims to improve the digital literacy of the people of Karang Panggung Village, Merigi Sakti Sub-district, Bengkulu Regency. Karang Panggung Village, Merigi Sakti Sub-district, Central Bengkulu Regency. Methods. used was a qualitative approach with surveys and socialisation to 30 randomly selected households. selected randomly. This activity includes education on digital financial management digital financial management, transaction security, and the utilisation of electronic payment applications. The results of the activities showed an increase in community understanding of the benefits, risks, and how to use digital transactions wisely. This programme has successfully encouraged the community of Karang Panggung Village to be more confident in adopting digital financial technology, support financial inclusion, and improve local economic welfare